Supercritical water reduction recovery method of waste lithium ion battery
Patent Information
- Application Number
- CN202111078191.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-15
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-09-15
AI Technical Summary
然而,该工艺首先需要将正负极分离,然后还需要进行氮气保护焙烧等预处理,导致该工艺处理流程长、处理成本高
① 不需要对废旧电池进行破碎、拆解等预处理过程,简化废旧锂离子电池回收工艺,操作简单;
Smart Images

Figure CN115939551B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery recycling, and in particular relates to a method for efficient recycling of waste lithium-ion batteries in a supercritical self-coupling system. Background Technology
[0002] With the large-scale application of lithium-ion batteries, their disposal volume is increasing year by year. Especially with the widespread use of lithium-ion batteries in electric vehicles, waste lithium-ion batteries will become one of the major urban solid wastes in my country. Lithium-ion batteries mainly consist of a positive electrode, a negative electrode, a separator, an electrolyte, and a metal casing. The positive electrode is mainly composed of ternary cathode materials, lithium cobalt oxide, lithium iron phosphate, and other positive electrode active materials, conductive carbon, and aluminum foil; the negative electrode is mainly composed of artificial graphite, natural graphite, and other negative electrode active materials, conductive carbon, and copper foil. Because the valuable metal content in waste batteries is much higher than in natural ores, and the impurity content is lower, waste lithium-ion batteries are figuratively called "urban minerals." On the other hand, nickel, cobalt, and manganese are heavy metals and are polluting, requiring proper disposal. Therefore, from both economic and environmental perspectives, efficient recycling of waste lithium-ion batteries can not only achieve resource recycling but also reduce environmental harm, which is of great significance in achieving good economic and ecological benefits.
[0003] Currently, the recycling of spent lithium-ion batteries mainly includes pyrometallurgical, hydrometallurgical, and combined pyrometallurgical and hydrometallurgical processes. Pyrometallurgical recycling involves adding appropriate amounts of coke and slagging agents to pyrometallurgically smelt spent lithium-ion batteries, converting valuable metals into elements or alloys. The positive and negative electrode conductive agents, as well as carbon materials such as graphite in the negative electrode, generally serve as fuel to provide a heat source and can also act as a reducing agent to reduce valuable metal elements in spent lithium-ion batteries to elements or oxides. Therefore, pyrometallurgical recycling is highly adaptable to raw materials, has a large processing capacity, and avoids complex mechanical dismantling and physical sorting, making it a relatively mature solution. However, pyrometallurgical processes are energy-intensive, generate large amounts of carbon dioxide greenhouse gases during processing, and can only recover some valuable metals such as cobalt, nickel, and copper from the batteries, while the recovery rate of carbonaceous components and lithium is low or not effectively recovered. Hydrometallurgical recycling involves leaching spent lithium-ion battery materials in acidic or alkaline aqueous solutions, followed by extraction using organic solvents, precipitation separation, and electrochemical deposition to extract metals and their compounds. However, wet recovery processes suffer from drawbacks such as difficult wastewater treatment, high reagent consumption, and high costs. Therefore, scholars have proposed a combined pyrometallurgical and hydrometallurgical recovery process. For example, Yang Y. et al. [Yang Y., Huang G., Xu S., et al. Thermal treatment process for the recovery of valuable metals from spent lithium-ion batteries[J]. Hydrometallurgy, 2016, 165: 39-396.] first separate the positive and negative electrode materials, then calcine them separately under a nitrogen atmosphere to remove the organic binder. After binder removal, the positive and negative electrode active materials and the current collector are separated by gravity separation. After separation, the positive electrode active material is leached using a sulfuric acid + hydrogen peroxide system, achieving leaching rates of 98%, 99%, and 84% for Ni, Co, and Mn, respectively. However, this process requires first separating the positive and negative electrodes, and then undergoing pretreatment such as nitrogen-protected calcination, resulting in a long processing flow and high processing costs.
[0004] In summary, current conventional recycling processes for spent lithium-ion batteries primarily focus on recovering the cathode material, exhibiting poor selectivity for metals. Subsequent multi-stage precipitation and extraction are necessary to obtain a relatively pure target product. Highly reactive lithium is frequently lost during separation and purification, resulting in significant waste of lithium resources. To obtain spent cathode powder, spent lithium batteries must undergo crushing pretreatment. However, the crushed lithium battery composition is complex, including cathode and anode powders, electrolyte, separator, and Al / Cu current collectors, greatly complicating cathode material separation. Furthermore, the electrolyte, accounting for approximately 12% of the battery cost, is highly volatile and decomposes during crushing, producing irritating and toxic gases that pose significant health and environmental hazards, making recycling and disposal difficult. The anode powder, accounting for approximately 20% of the total battery cost, is also poorly managed, either sold at low prices or used as a carbonaceous reducing agent during pretreatment. Therefore, there is a need to develop new, efficient recycling technologies for spent lithium-ion batteries to achieve short-process, low-energy, and highly selective recovery of all valuable components. Summary of the Invention
[0005] To address the problems existing in the prior art, the present invention aims to provide a supercritical water reduction and recycling method for waste lithium-ion batteries, which is based on a novel mechanism to recycle waste lithium-ion batteries in a simple and efficient manner.
[0006] A supercritical water reduction and recycling method for waste lithium-ion batteries involves heating a mixture of waste lithium-ion battery cells and water in a sealed container to the supercritical state of water to carry out a supercritical reduction reaction. After the reaction is completed, a lithium-rich solution, a current collector, and delithiated electrode materials are separated from the mixture.
[0007] The technical solution of this invention supercritically couples the treatment of electrolyte and separator in the battery cell with the treatment of positive and negative electrodes. It utilizes the supercritical water reducing fluid atmosphere created by the supercritical water reaction of the electrolyte and separator, and innovatively uses this supercritical water reducing fluid atmosphere to treat the positive and negative electrodes. In this way, not only can the treatment of electrolyte and separator in the battery cell be realized, but also the positive and negative electrodes can be better recycled and restructured based on the new supercritical water reducing fluid atmosphere; the recovery rate of positive electrode materials is improved, and the reuse performance of recycled materials is improved.
[0008] This invention can theoretically be applied to the recycling and processing of all types of waste lithium-ion battery cells. For example, the waste lithium-ion battery can be at least one of the following: nickel-cobalt-manganese ternary batteries, lithium iron phosphate batteries, lithium cobalt oxide batteries, and lithium manganese oxide batteries.
[0009] In this invention, the battery cell comprises a positive electrode, a separator, and a negative electrode sequentially laminated together, and an electrolyte solution for soaking the positive electrode, the separator, and the negative electrode. Preferably, the battery cell component is an intact, unbroken battery cell. That is, the battery cell is in the packaged form of a used battery.
[0010] Preferably, the residual voltage of the battery cell is less than or equal to 1V, more preferably 0-0.5V; and even more preferably 0-0.1V.
[0011] Preferably, the solid-liquid ratio of the battery cell to water is (0.1~25):100 (g:ml); more preferably (5~10):100 (g:ml).
[0012] In this invention, an auxiliary agent is also added to the mixture, which is at least one selected from alcohols, ethers, esters, nitriles, and ketones. This invention has found that adding a certain amount of auxiliary agent during the treatment process helps to further improve the supercritical reduction recovery treatment effect.
[0013] The additive is at least one of alcohols, ethers, esters, nitriles, and ketones with a carbon number of 20 or less, preferably 10 or less.
[0014] Preferably, the alcohol is at least one of C1-C6 units or polyols, for example, it may be at least one of methanol, ethanol, propanol, isopropanol, 1-butanol, propylene glycol, glycerol, etc.
[0015] Preferably, the ether is at least one of a C2-C6 monoether, polyether, or cyclic ether; for example, it may be at least one of dimethyl ether, diethyl ether, methyl ethyl ether, oxocyclopentane, and oxocyclohexane.
[0016] Preferably, the ester is C2~C 10 Carboxylic acid esters ( C3~C 10 carbonates ( At least one of the following: ; in addition, the ester may also be a carboxylic acid ester or a carbonate lactone. In the structure, R1 is H, a C1-C6 alkyl group, or a C3-C6 cycloalkyl group; R2 and R3 are C1-C6 alkyl groups or C3-C6 cycloalkyl groups; or R1 and R2 are cyclized to form a five- or six-membered ring including C(O)-O; R2 and R3 are cyclized to form a five- or six-membered ring including -OC(O)-O.
[0017] Preferably, the nitrile is a C2-C4 nitrile; for example, it may be at least one of acetonitrile, propionitrile, etc.
[0018] Preferably, the ketone is C3~C6. 10 It can be at least one of monoketones, polyketones, and cyclic ketones; for example, it can be at least one of acetone, 2-butanone, 3-pentanone, cyclopentanone, cyclohexanone, etc.
[0019] More preferably, the additive is at least one selected from methanol, ethanol, carbonates, diethyl ether, acetonitrile, and acetone.
[0020] In this invention, the auxiliary agent is preferably a combination of two or more of alcohols, ethers, esters, nitriles, and ketones.
[0021] Studies have found that using a combination of additives can help achieve synergy with supercritical reduction processes, and can help improve the treatment effect at lower dosages, especially the recovery rate of various elements in the positive electrode. It can also unexpectedly improve the microstructure and surface properties of the negative electrode material, which helps to improve the electrochemical performance of the regenerated negative electrode.
[0022] In this invention, when the additive is a combination additive, it is preferably a combination of different types of substances.
[0023] Preferably, the weight ratio of the additive to the battery cell is 0.01 to 1:1; more preferably, it is 0.2 to 0.5:1.
[0024] Preferably, the temperature of the supercritical state is 350-750℃, more preferably 550-750℃; the pressure is 15-50MPa, more preferably 25-50 MPa.
[0025] Preferably, the supercritical reduction reaction time is 2-10 h, and more preferably 5-8 h.
[0026] In this invention, the system after the supercritical reduction reaction is sieved to obtain the current collector sieve residue and a slurry containing electrode materials; the slurry is then subjected to solid-liquid separation to obtain a lithium-rich solution and delithiated electrode materials. Alternatively, the system after the supercritical reduction reaction can be subjected to solid-liquid separation to obtain a lithium-rich solution and reduction residue. The reduction residue can then be dried and sieved to obtain a current collector and a delithiation electrode material.
[0027] In this invention, lithium can be recovered from lithium-rich solutions using existing methods.
[0028] For example, lithium precipitation treatment can be performed on lithium-rich solutions to recover the lithium. Preferably, a lithium precipitation agent is added to the lithium-rich solution to perform lithium precipitation treatment and recover the lithium therein; Preferably, the lithium precipitation agent is at least one of sodium carbonate and potassium carbonate.
[0029] In this invention, existing methods can also be used to process the delithiation electrode material.
[0030] Preferably, the delithiated electrode material is subjected to acid leaching treatment, followed by solid-liquid separation to obtain electrode material leachate and carbon slag.
[0031] For example, the acid used in the acid leaching process can be a strong inorganic acid, such as sulfuric acid; the acid concentration can be, for example, from 0.5M to saturation concentration. The acid leaching solution can be directly adjusted in proportion for co-precipitation recovery to obtain the cathode material, or it can be separately recovered and purified using existing methods. For example, when the acid leaching solution contains Mn, P2O4 can be used for extraction, and the volume of P2O4 in the extractant during the extraction process can be, for example, 30-40%; the saponification rate is 70-85%; and the pH is 3.5-4.0.
[0032] When the acid leachate contains Co, the extractant can be P507, with the volume content of P507 in the extracted organic phase being, for example, 10-30%; the degree of saponification being 60-80%; and the pH being 4-5. Conversely, when the acid leachate contains Ni, the extractant can be P507, with the volume content of P507 in the extracted organic phase being, for example, 10-30%; the degree of saponification being 20-40%; and the pH being 1.5-3.
[0033] The preferred technical solution of the present invention includes the following steps: Step (1): The waste lithium-ion batteries are pre-discharged physically; further, the physical discharge is to connect the battery pack to a discharge device and discharge it to 0-0.5V; preferably, to 0-0.1V.
[0034] Step (2): The supercritical reduction reaction of discharged waste batteries in a supercritical self-coupling system; further, the supercritical self-coupling system is composed of waste batteries and water, and the solid-liquid ratio of the battery to water in the system is (0.1~25):100 (g:ml), preferably (5~10):100 (g:ml); further, the supercritical reduction reaction conditions are a temperature of 350-750℃, a pressure of 15-50MPa, and a supercritical reduction reaction time of 2-10 h; preferably, the supercritical reduction reaction temperature is 550-750℃, the pressure is 25-50 MPa, and the supercritical reduction reaction time is 5-8 h.
[0035] Step (3): The process includes solid-liquid phase separation of the supercritical reduction reaction products, recovery of lithium from the separated liquid phase, and recovery of various components from the solid phase. Specifically, the solid-liquid phase separation of the supercritical reduction reaction products involves first using wet crushing to break large-sized components in the supercritical reduction reaction products to 0.1 mm to 100 mm, preferably to 1-5 mm; then, placing the crushed products in a 240-400 mesh wet vibrating sieve for separation by vibration. The material over the sieve consists of copper foil, aluminum foil, and battery casing, while the material under the sieve is a lithium-containing slurry containing positive and negative electrode powders; finally, the material under the sieve is subjected to solid-liquid separation using conventional methods such as plate and frame filter press or centrifugal filtration. The filtrate is a lithium-containing solution, and the filter cake mainly consists of positive and negative electrode materials. Furthermore, the recovery of lithium from the liquid phase refers to using conventional precipitation or evaporation crystallization methods to recover lithium from the solution obtained through solid-liquid separation using conventional methods such as plate and frame filter press or centrifugal filtration. Furthermore, the separation of components in the solid phase includes the following: ① After drying the material on the wet vibrating screen, it is first demagnetized, and then the copper foil and aluminum foil are separated and recovered using sorting technology; ② The filter cake, whose main components are positive and negative electrode materials, is subjected to conventional acid leaching, and valuable metals are recovered from the acid leaching solution. The acid leaching residue is high-purity carbon powder.
[0036] In another embodiment of the present invention, waste black powder from spent lithium-ion batteries is obtained. This waste black powder, water, and additives are then mixed to obtain a mixture. The mixture is then subjected to supercritical reduction and recycling treatment according to the mixture treatment method described in the first embodiment above. The resulting lithium-containing solution and delithiated electrode materials can also be recycled using the above method.
[0037] In this invention, the waste black powder is a mixture containing positive and negative electrode materials. It can be obtained by disassembling the battery cell and performing current collector stripping processes using existing methods.
[0038] The technical solution of this invention, through its process method, achieves the following effects without prior crushing and separation of the components of waste lithium batteries: ① The electrolyte is completely degraded in a supercritical self-coupling system, avoiding the difficult electrolyte disposal problem that is hard to avoid in traditional battery dismantling; ② Lithium in waste batteries is preferentially and selectively recovered in almost all quantities; ③ Copper and aluminum are fully recovered in metallic form; ④ Valuable elements such as cobalt, nickel, and manganese in waste batteries can be fully leached with low acid; ⑤ Carbonaceous components in waste batteries are recovered in the form of high-purity carbon.
[0039] The novel method for efficient recycling of spent lithium-ion batteries in a supercritical self-coupling system proposed in this invention achieves complete degradation of the electrolyte in a supercritical self-coupling system without the need for crushing and separating the components of the spent batteries. This method results in almost complete recovery of lithium with preferential selectivity, complete recovery of copper and aluminum in their metallic form, complete low-acid leaching of valuable elements, and recovery of carbonaceous components in the form of high-purity carbon. This is because the supercritical reduction reaction temperature used in this invention is 350-750℃. Within this temperature range, the spent battery cells spontaneously crack, releasing the components and triggering the following corresponding reactions: (1) Ester compounds in the electrolyte (referring to ethylene carbonate, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate, etc., which can be represented by the molecular formula C) x H y O z The electrolyte, upon contact with water, undergoes a reaction similar to supercritical water hydrogen production from biomass, generating carbon dioxide, methane, and hydrogen. The produced methane then undergoes further steam reforming to produce hydrogen and carbon monoxide. This process achieves the degradation of ester compounds in the electrolyte. The main reaction equations are as follows: C x H y O z + H2O(g) CO2(g) + CH4(g) + H2(g) CH4 + H2O(g) = H2(g) + CO(g) (2) The LiPF6 electrolyte in the electrolyte solution undergoes decomposition and hydrolysis in the supercritical water system, and also reacts with the aluminum current collector. The corresponding products enter the liquid phase, thus achieving the harmless disposal of LiPF6. The main reactions in this process are as follows: LiPF6 LiF + PF5 → PF5 + 4H2O 5HF + H3PO4, 6HF + 2Al 2AlF3+ 3H2 (3) The diaphragm degrades and carbonizes under supercritical high temperature conditions, forming a carbonaceous component together with the negative electrode powder. Part of this carbonaceous component reacts with water vapor to produce H2 and CO gas. The unreacted carbon remains in the slag phase and is regenerated into high-purity carbon powder after subsequent acid leaching to remove impurities. (4) Additional additives can further enhance the treatment effect of supercritical reducing atmosphere. (5) The H2 and CO reducing gases produced by the above series of reactions can complete the one-pot reduction of valuable metals in the positive electrode. Li is released from the original layered structure into the aqueous solution to achieve preferential selective recovery of lithium, while valuable metals such as Ni, Co, and Mn are reduced to a low valence state that is easy to leach out, and are retained in the slag phase and recovered by low acid leaching. (6) The aluminum foil reacts with water vapor in the initial stage to generate Al(OH)3. The reaction continues to generate a protective film Al2O3 and prevents the reaction from happening further. The copper foil does not react with water vapor. Therefore, large pieces of aluminum foil and copper foil do not participate in the reaction and remain in the solid slag. They are mechanically separated in the post-processing steps.
[0040] Therefore, this invention proposes a method for the efficient recycling of spent lithium-ion batteries based on supercritical water fluid, which has the following advantages and positive effects compared with the prior art: ① No pre-treatment process such as crushing and dismantling of waste batteries is required, simplifying the recycling process of waste lithium-ion batteries and making the operation simple; ② The electrolyte, electrolyte, and separator components in the waste batteries are degraded and carbonized in the supercritical water treatment system, ensuring the environmentally friendly recycling of waste batteries; ③ The hydrogen and reducing gases such as carbon monoxide produced by the electrolyte and other components in the supercritical system reduce the valuable metals such as Ni, Co, and Mn in the positive electrode to a low valence state that is easy to leach, creating conditions for the subsequent low-acid leaching of these elements. ④ Aluminum and copper foils can be recycled in large sizes, lithium can be fully recovered in the liquid phase of a supercritical system, and carbonaceous components in waste batteries can be recovered in the form of high-purity carbon.
[0041] Obviously, this invention can achieve the harmless treatment of waste batteries and the low-cost full recovery of valuable components. Attached Figure Description
[0042] Figure 1 This is a schematic diagram of the experimental procedure; Detailed Implementation
[0043] The present invention will be further described in detail below with reference to specific embodiments, but the present invention is not limited to the following embodiments.
[0044] Example 1: ①Physical discharge: The waste nickel-cobalt-manganese ternary lithium battery (NCM111) is directly physically discharged to 0.2V, and the plastic shell is manually removed to obtain 40g of waste battery cells; ② Supercritical reduction reaction: Place the above-mentioned waste battery cells into a 1L high-temperature and high-pressure reactor. The reactor is made of Inconel 625 alloy. After submerging the waste battery cells with 400mL of water, seal the reactor. Turn on the heating furnace and constant flow pump to heat and pressurize the reactor, maintaining the reactor temperature at 405℃ and the pressure at 25MPa. React under these conditions for 3 hours. ③ Solid-liquid separation: After the reaction is completed, wait for the temperature inside the vessel to drop to room temperature, open the exhaust valve, and after the pressure drops to atmospheric pressure, open the reaction vessel, collect the solution inside the vessel and filter it to obtain a lithium-containing solution and a pot of reduction residue; ④ Lithium carbide precipitation: Add excess Na2CO3 (excess coefficient 1.50) to the above lithium-containing solution, stir at 90℃ for 30 min, and filter while hot to obtain Li2CO3; ⑤ After drying and conventionally dispersing the slag phase (one pot of reduction slag) from the previous step, it is then placed in a vibrating separator screen for vibrating treatment. The screen mesh size of the vibrating separator screen used in this step is 240-400 mesh. The material on the screen is large copper foil and aluminum foil, and the material under the screen is electrode powder. ⑥ Perform acid leaching on the electrode powder obtained in the previous step. Take an appropriate amount of the above electrode powder and add it to 500 mL of 1 mol L⁻¹ solution at a liquid-to-solid ratio (mL:g) of 20:1. -1 In an H2SO4 solution, the mixture was heated to 60°C and reacted for 1 hour. After filtration and washing, an acid leaching solution and an acid leaching residue (carbon residue) were obtained. Solid-liquid separation was then performed on the residue. Solid-liquid separation yields a leachate. The leachate is first subjected to Na soap-treated P204 extraction to remove manganese, followed by back-extraction to obtain a manganese sulfate solution. Then, the solution is subjected to saponification with P507 to extract cobalt, followed by back-extraction to obtain a cobalt sulfate solution. The cobalt-extracted solution is then subjected to saponification with P507 to extract nickel, followed by back-extraction to obtain a nickel sulfate solution. Details are as follows: (1) First, P2O4 was used to extract Mn: kerosene was used as a diluent, and the volume concentration of P2O4 was 35%; before extraction, NaOH solid was used for saponification, and the saponification rate was 75%; pH = 3.5-4.0; O / A (volume ratio of organic phase to aqueous phase) ratio 3:1; shaking time 1h. Back-extraction: 3 mol / L H2SO4 was added to the extract, and after thorough shaking, it was allowed to stand. 2+ It enters the aqueous phase to obtain MnSO4.
[0045] (2) P507 extraction of Co: Kerosene was used as a diluent, and the volume concentration of P507 was 20%; NaOH solid was used for saponification before extraction, with a saponification rate of 70%; pH=4.2; O / A (volume ratio of organic phase to aqueous phase) ratio 1:1; shaking time 20 min. Back-extraction: 2 mol / L H2SO4 was added to the extract, and after thorough shaking, it was allowed to stand. 2+ It enters the aqueous phase to obtain CoSO4.
[0046] (3) Ni extraction with P507: Kerosene was used as a diluent, and the volume concentration of P507 was 20%; NaOH solid was used for saponification before extraction, with a saponification rate of 30%; pH=2.1; O / A (organic phase to aqueous phase volume ratio) ratio 1:1; shaking time 10 min. Back-extraction: 2 mol / L H2SO4 was added to the extract, and after thorough shaking, it was allowed to stand. 2+ It enters the aqueous phase to obtain NiSO4.
[0047] The tests showed that the leaching rates of manganese, cobalt, and nickel were 85.6%, 84.4%, and 82.5%, respectively; the extraction rate of lithium was 82.4%; and the recovery rates of copper foil and aluminum foil were 85.3% and 81.3%, respectively.
[0048] ⑥ The slag phase (carbon slag) obtained from solid-liquid separation is dried and dispersed using conventional methods to obtain high-purity carbon powder. Results show that the fixed carbon content in the obtained carbon powder is 84.2%. When this material is assembled into a CR2032 lithium coin cell according to the national standard GB / T 24533-2009, tests show that the reversible specific capacity of this electrode under 0.2C conditions is 291 mAh / g.
[0049] Example 2: Compared with Example 1, the only difference is that methanol is added as an additive in the supercritical reduction process. The difference in step ② is as follows: Supercritical reduction reaction: The above-mentioned waste battery cells are placed in a 1L high-temperature and high-pressure reactor. The reactor is made of Inconel 625 alloy. 400mL of water and 15g of methanol are introduced into the reactor to submerge the waste battery cells. The reactor is then sealed. The heating furnace and constant flow pump are turned on to heat and pressurize the reactor, maintaining the reactor temperature at 405℃ and the pressure at 25MPa. The reaction is carried out under these conditions for 3 hours. Other steps and processes are the same as in Example 1.
[0050] Tests showed that the leaching rates of manganese, cobalt, and nickel were 98.4%, 99.1%, and 98.3%, respectively; the extraction rate of lithium was 99.2%; and the recovery rates of copper foil and aluminum foil were 98.1% and 98.9%, respectively.
[0051] The slag phase (carbon slag) obtained from solid-liquid separation was dried and dispersed using conventional methods to obtain high-purity carbon powder. Results showed that the fixed carbon content in the obtained carbon powder was 94.3%. When this material was assembled into a CR2032 lithium coin cell according to the national standard GB / T 24533-2009, tests showed that the reversible specific capacity of this electrode under 0.2C conditions was 345 mAh / g.
[0052] Example 3: Compared with Example 1, the only difference is that methanol and ethylene carbonate are added as synergistic agents in the supercritical reduction process. The difference in step ② is as follows: Supercritical reduction reaction: The above-mentioned waste battery cells are placed in a 1L high-temperature and high-pressure reactor. The reactor is made of Inconel 625 alloy. 400mL of water, 8g of methanol, and 7g of ethylene carbonate are introduced into the reactor to submerge the waste battery cells. The reactor is then sealed. The heating furnace and constant flow pump are turned on to heat and pressurize the reactor, maintaining the reactor temperature at 405℃ and the pressure at 25MPa. The reaction is carried out under these conditions for 3 hours. Other steps and conditions are the same as in Example 1.
[0053] Tests showed that the leaching rates of manganese, cobalt, and nickel were 99.6%, 99.4%, and 99.3%, respectively; the extraction rate of lithium was 99.5%; and the recovery rates of copper foil and aluminum foil were 99.2% and 99.1%, respectively.
[0054] The slag phase (carbon slag) obtained from solid-liquid separation was dried and dispersed using conventional methods to obtain high-purity carbon powder. Results showed that the fixed carbon content in the obtained carbon powder was 99.3%. When this material was assembled into a CR2032 lithium coin cell according to the national standard GB / T 24533-2009, tests showed that the reversible specific capacity of this electrode under 0.2C conditions was 354 mAh / g.
[0055] As can be seen from Examples 1-3, full recovery can be achieved through supercritical reduction. With the assistance of additives, especially alcohols and carbonates, the full recovery effect can be significantly improved. For example, the recovery rate of cathode elements can be improved, and the graphite structure can be cleared, thereby improving the recovery rate and regeneration performance of the recovered graphite.
[0056] Example 4: ①Physical discharge: The waste lithium manganese oxide batteries are directly physically discharged to 0.1V, and the plastic shell is manually removed to obtain 50g of waste battery cells; ② Supercritical reduction reaction: Place the above-mentioned waste battery cells into a 1L high-temperature and high-pressure reactor. The reactor is made of Inconel 625 alloy. 500mL of water and 20g of acetone are introduced into the reactor to submerge the waste battery cells. After sealing the reactor, turn on the heating furnace and constant flow pump to heat and pressurize the reactor. Maintain the reactor temperature at 550℃ and the pressure at 30MPa. React under these conditions for 5 hours. ③ Solid-liquid separation: After the reaction is completed, wait for the temperature inside the vessel to drop to room temperature, open the exhaust valve, and after the pressure drops to atmospheric pressure, open the reaction vessel, collect the solution inside the vessel and filter it to obtain a lithium-containing solution and a pot of reduction residue; ④ Lithium carbide precipitation: Add excess Na2CO3 (excess coefficient 1.4) to the above lithium-containing solution, stir at 90℃ for 30 min, and filter while hot to obtain Li2CO3; ⑤ After drying the slag phase (one pot of reduction slag) from the previous step, it is subjected to conventional dispersing treatment and then placed in a vibrating separator screen for vibrating treatment. The screen mesh size of the vibrating separator screen used in this step is 240-400 mesh. The material on the screen is large copper foil and aluminum foil, and the material under the screen is electrode powder. ⑥ Perform acid leaching on the electrode powder obtained in the previous step. Take an appropriate amount of the above electrode powder and add it to 500 mL of 1 mol L⁻¹ solution at a liquid-to-solid ratio (mL:g) of 20:1. -1 The acid leaching solution and acid leaching residue (carbon residue) were obtained by heating to 60°C and reacting for 1 hour in H2SO4 solution, followed by filtration and washing. Solid-liquid separation was then performed on the acid leaching solution and acid leaching residue (carbon residue).
[0057] Solid-liquid separation yields a leachate. The leachate is first subjected to Na soap followed by P2O4 extraction to remove manganese. After back-extraction, a manganese sulfate solution is obtained. Details are as follows: Mn was extracted using P2O4: kerosene was used as the diluent, and the P2O4 volume concentration was 35%; saponification was performed using solid NaOH before extraction, with a saponification rate of 75%; pH = 3.5-4.0; O / A (organic phase to aqueous phase volume ratio) ratio 3:1; shaking time 1 h. Back-extraction: 3 mol / L H2SO4 was added to the extract, and after thorough shaking, it was allowed to stand. 2+ It enters the aqueous phase to obtain MnSO4.
[0058] Tests showed that the leaching rate of manganese was 98.6%; the extraction rate of lithium was 98.9%; and the recovery rates of copper foil and aluminum foil were 98.2% and 98.5%, respectively.
[0059] The slag phase (carbon slag) obtained from solid-liquid separation was dried and dispersed using conventional methods to obtain high-purity carbon powder. Results showed that the fixed carbon content in the obtained carbon powder was 94.7%. When this material was assembled into a CR2032 lithium coin cell according to the national standard GB / T 24533-2009, tests showed that the reversible specific capacity of this electrode under 0.2C conditions was 347 mAh / g.
[0060] Example 5: Compared with Example 4, the only difference is that a composite additive of acetone and ethyl acetate is added in the supercritical reduction reaction stage. The difference in step ② is as follows: the above-mentioned waste battery cells are placed in a 1L high-temperature and high-pressure reactor. The reactor is made of Inconel 625 alloy. 500mL of water, 10g of acetone, and 5g of methyl acetate are introduced into the reactor to submerge the waste battery cells. The reactor is then sealed. The heating furnace and constant flow pump are turned on to heat and pressurize the reactor, maintaining the reactor temperature at 550℃ and the pressure at 30MPa. The reaction is carried out under these conditions for 5 hours. Other process steps and parameters are the same as in Example 4.
[0061] Tests showed that the leaching rate of manganese was 99.3%; the extraction rate of lithium was 99.2%; and the recovery rates of copper foil and aluminum foil were 99.3% and 99.6%, respectively.
[0062] The slag phase (carbon slag) obtained from solid-liquid separation was dried and dispersed using conventional methods to obtain high-purity carbon powder. Results showed that the fixed carbon content in the obtained carbon powder was 99.4%. When this material was assembled into a CR2032 lithium coin cell according to the national standard GB / T 24533-2009, tests showed that the reversible specific capacity of this electrode under 0.2C conditions was 355 mAh / g.
[0063] Example 6: ①Physical discharge: The waste lithium cobalt oxide is directly physically discharged to 0.1V, and the plastic shell is manually removed to obtain 60g of waste battery cells; ② Supercritical reduction reaction: Place the above-mentioned waste battery cells into a 1L high-temperature and high-pressure reactor. The reactor is made of Inconel 625 alloy. 500mL of water and 20g of ethylene carbonate are introduced into the reactor to submerge the waste battery cells. After sealing the reactor, turn on the heating furnace and constant flow pump to heat and pressurize the reactor. Maintain the reactor temperature at 600℃ and the pressure at 30MPa. React under these conditions for 6 hours. ③ Solid-liquid separation: After the reaction is completed, wait for the temperature inside the vessel to drop to room temperature, open the exhaust valve, and after the pressure drops to atmospheric pressure, open the reaction vessel, collect the solution inside the vessel and filter it to obtain a lithium-containing solution and a pot of reduction residue; ④ Lithium carbide precipitation: Add excess Na2CO3 (excess coefficient 1.50) to the above lithium-containing solution, stir at 90℃ for 30 min, and filter while hot to obtain Li2CO3; ⑤ After drying the slag phase (one pot of reduction slag) from the previous step, it is subjected to conventional dispersing treatment and then placed in a vibrating separator screen for vibrating treatment. The screen mesh size of the vibrating separator screen used in this step is 240-400 mesh. The material on the screen is large copper foil and aluminum foil, and the material under the screen is electrode powder. ⑥ Perform acid leaching on the electrode powder obtained in the previous step. Take an appropriate amount of the above electrode powder and add it to 500 mL of 1 mol L⁻¹ solution at a liquid-to-solid ratio (mL:g) of 20:1. -1 The mixture was heated to 60°C and reacted for 1 hour in an H2SO4 solution. After filtration and washing, acid leaching solution and acid leaching residue (carbon residue) were obtained. Solid-liquid separation was then performed on these residues. Solid-liquid separation yields a leachate. The leachate is first subjected to Na soap extraction followed by P507 extraction to remove cobalt. After back-extraction, a cobalt sulfate solution is obtained. Details are as follows: P504 extraction of Co: Kerosene was used as a diluent, and the volume concentration of P507 was 20%; saponification was performed using solid NaOH before extraction, with a saponification rate of 70%; pH=4.2; O / A (organic phase to aqueous phase volume ratio) ratio 1:1; shaking time 20 min. Back-extraction: 2 mol / L H2SO4 was added to the extract, and after thorough shaking, it was allowed to stand. 2+ It enters the aqueous phase to obtain CoSO4.
[0064] Tests showed that the cobalt leaching rate was 98.2%, the lithium extraction rate was 99.1%, and the recovery rates of copper foil and aluminum foil were 98.3% and 98.4%, respectively.
[0065] The slag phase (carbon slag) obtained from solid-liquid separation is dried and dispersed using conventional methods to obtain high-purity carbon powder. Results show that the fixed carbon content in the obtained carbon powder is 95.6%. Testing with lithium button cells shows that when this carbon powder is used as an electrode, the reversible specific capacity of the electrode under 0.2C conditions is 349 mAh / g.
[0066] Example 7: Compared with Example 6, the only difference is that a composite additive of ethylene carbonate and acetonitrile is added in the supercritical reduction reaction stage. The difference in step ② is as follows: the above-mentioned waste battery cells are placed in a 1L high-temperature and high-pressure reactor. The reactor is made of Inconel 625 alloy. 500mL of water, 10g of ethylene carbonate, and 8g of acetonitrile are introduced into the reactor to submerge the waste battery cells. The reactor is then sealed. The heating furnace and constant flow pump are turned on to heat and pressurize the reactor, maintaining the reactor temperature at 600℃ and the pressure at 30MPa. The reaction is carried out under these conditions for 6 hours. Other processes and steps are the same as in Example 6.
[0067] Tests showed that the cobalt leaching rate was 99.5%, the lithium extraction rate was 99.6%, and the recovery rates of copper foil and aluminum foil were 99.3% and 99.5%, respectively.
[0068] The slag phase (carbon slag) obtained from solid-liquid separation is dried and dispersed using conventional methods to obtain high-purity carbon powder. Results show that the obtained carbon powder contains 99.5% fixed carbon. Testing with lithium button cells shows that when this carbon powder is used as an electrode, the reversible specific capacity at 0.2C is 356 mAh / g.
[0069] Example 8: ①Physical discharge: The waste nickel-cobalt-manganese ternary lithium battery (NCM532) is directly physically discharged to 0.3V, and the plastic shell is manually removed to obtain 50g of waste battery cells; ② Supercritical reduction reaction: Place the above-mentioned waste battery cells into a 2L high-temperature and high-pressure reactor. The reactor is made of Inconel 625 alloy. 1000mL of water and 10g of ethyl formate are introduced into the reactor to submerge the waste battery cells. After sealing the reactor, turn on the heating furnace and constant flow pump to heat and pressurize the reactor. Maintain the reactor temperature at 700℃ and the pressure at 30MPa. React under these conditions for 6 hours. ③ Solid-liquid separation: After the reaction is completed, wait for the temperature inside the vessel to drop to room temperature, open the exhaust valve, and after the pressure drops to atmospheric pressure, open the reaction vessel, collect the solution inside the vessel and filter it to obtain a lithium-containing solution and a pot of reduction residue; ④ Lithium carbide precipitation: Add excess Na2CO3 (excess coefficient 1.50) to the above lithium-containing solution, stir at 90℃ for 30 min, and filter while hot to obtain Li2CO3; ⑤ After drying the slag phase (one pot of reduction slag) from the previous step, perform conventional dispersing treatment, and then place it in a vibrating separator screen for vibrating treatment. The screen mesh size of the vibrating separator screen used in this step is 240-400 mesh. The material on the screen is large copper foil and aluminum foil, and the material under the screen is electrode powder. ⑥ Perform acid leaching on the electrode powder obtained in the previous step. Take an appropriate amount of the above electrode powder and add it to 500 mL of 1 mol L⁻¹ solution at a liquid-to-solid ratio (mL:g) of 20:1. -1 In an H2SO4 solution, the mixture was heated to 60°C and reacted for 1 hour. After filtration and washing, an acid leaching solution and an acid leaching residue (carbon residue) were obtained. Solid-liquid separation was then performed on the residue. Solid-liquid separation yields a leachate. The leachate is first subjected to Na soap-treated P2O4 to extract manganese, followed by back-extraction to obtain a manganese sulfate solution. Then, it is subjected to saponified P5O7 to extract cobalt, followed by back-extraction to obtain a cobalt sulfate solution. The cobalt-extracted solution is then subjected to saponified P5O7 to extract nickel, followed by back-extraction to obtain a nickel sulfate solution. See Example 1 for details.
[0070] Tests showed that the leaching rates of manganese, cobalt, and nickel were 98.6%, 98.9%, and 98.7%, respectively. The extraction rate of lithium was 98.9%, and the recovery rates of copper foil and aluminum foil were 98.3% and 98.4%, respectively.
[0071] The slag phase (carbon slag) obtained from solid-liquid separation is dried and dispersed using conventional methods to obtain high-purity carbon powder. Results show that the fixed carbon content in the obtained carbon powder is 96.1%. Testing with lithium button cells shows that when this carbon powder is used as an electrode, the reversible specific capacity of the electrode under 0.2C conditions is 348 mAh / g.
[0072] Example 9: Compared with Example 8, the only difference is that a composite auxiliary of ethyl formate and ethanol is added in the supercritical reduction reaction stage, and the difference in step ② is: ② Supercritical reduction reaction: The above-mentioned waste battery cells were placed in a 2L high-temperature and high-pressure reactor. The reactor was made of Inconel 625 alloy. 1000mL of water, 10g of ethyl formate, and 6g of ethanol were introduced into the reactor to submerge the waste battery cells. The reactor was then sealed. The heating furnace and constant flow pump were turned on to heat and pressurize the reactor, maintaining the reactor temperature at 700℃ and the pressure at 30MPa. The reaction was carried out under these conditions for 6 hours. Other processes and parameters were the same as in Example 8.
[0073] Tests showed that the leaching rates of manganese, cobalt, and nickel were 99.7%, 99.4%, and 99.6%, respectively. The extraction rate of lithium was 99.3%, and the recovery rates of copper foil and aluminum foil were 99.2% and 99.4%, respectively.
[0074] The slag phase (carbon slag) obtained from solid-liquid separation is dried and dispersed using conventional methods to obtain high-purity carbon powder. Results show that the obtained carbon powder contains 99.3% fixed carbon. Testing with lithium button cells shows that when this carbon powder is used as an electrode, the reversible specific capacity at 0.2C is 352 mAh / g.
[0075] Example 10: ①Physical discharge: The waste nickel-cobalt-manganese ternary lithium battery (NCM622) is directly physically discharged to 0.1V, and the plastic shell is manually removed to obtain 40g of waste battery cells; ② Supercritical reduction reaction: Place the above-mentioned waste battery cells into a 2L high-temperature and high-pressure reactor. The reactor is made of Inconel 625 alloy. 800mL of water and 15g of diethyl carbonate are introduced into the reactor to submerge the waste battery cells. After sealing the reactor, turn on the heating furnace and constant flow pump to heat and pressurize the reactor. Maintain the reactor temperature at 500℃ and the pressure at 25MPa. React under these conditions for 8 hours. ③ Solid-liquid separation: After the reaction is completed, wait for the temperature inside the vessel to drop to room temperature, open the exhaust valve, and after the pressure drops to atmospheric pressure, open the reaction vessel, collect the solution inside the vessel and filter it to obtain a lithium-containing solution and a pot of reduction residue; ④ Lithium carbide precipitation: Add excess Na2CO3 (excess coefficient 1.50) to the above lithium-containing solution, stir at 90℃ for 30 min, and filter while hot to obtain Li2CO3; ⑤ After drying the slag phase (one pot of reduction slag) from the previous step, it is subjected to conventional dispersing treatment and then placed in a vibrating separator screen for vibrating treatment. The screen mesh size of the vibrating separator screen used in this step is 240-400 mesh. The material on the screen is large copper foil and aluminum foil, and the material under the screen is electrode powder. ⑥ Perform acid leaching on the electrode powder obtained in the previous step. Take an appropriate amount of the above electrode powder and add it to 500 mL of 1 mol L⁻¹ solution at a liquid-to-solid ratio (mL:g) of 20:1. -1The acid leaching solution and acid leaching residue (carbon residue) were obtained by heating to 60°C and reacting for 1 hour in H2SO4 solution, followed by filtration and washing. Solid-liquid separation was then performed on the acid leaching solution and acid leaching residue (carbon residue).
[0076] Solid-liquid separation yields a leachate. The leachate is first subjected to Na soap-treated P2O4 to extract manganese, followed by back-extraction to obtain a manganese sulfate solution. Then, it is subjected to saponified P5O7 to extract cobalt, followed by back-extraction to obtain a cobalt sulfate solution. The cobalt-extracted solution is then subjected to saponified P5O7 to extract nickel, followed by back-extraction to obtain a nickel sulfate solution. See Example 1 for details.
[0077] Tests showed that the leaching rates of manganese, cobalt, and nickel were 98.2%, 98.7%, and 98.6%, respectively. The extraction rate of lithium was 98.8%, and the recovery rates of copper foil and aluminum foil were 98.9% and 98.7%, respectively.
[0078] The slag phase (carbon slag) obtained from solid-liquid separation is dried and dispersed using conventional methods to obtain high-purity carbon powder. Results show that the fixed carbon content in the obtained carbon powder is 96.3%. Testing with lithium button cells shows that when this carbon powder is used as an electrode, the reversible specific capacity of the electrode under 0.2C conditions is 349 mAh / g.
[0079] Example 11: Compared with Example 10, the only difference is that a composite auxiliary of diethyl carbonate and acetic acid is added in the supercritical reduction reaction stage, and the difference in step ② is: Tests showed that the leaching rates of manganese, cobalt, and nickel were 99.4%, 99.8%, and 99.7%, respectively. The extraction rate of lithium was 99.2%, and the recovery rates of copper foil and aluminum foil were 99.4% and 99.5%, respectively.
[0080] The slag phase (carbon slag) obtained from solid-liquid separation is dried and dispersed using conventional methods to obtain high-purity carbon powder. Results show that the obtained carbon powder contains 99.7% fixed carbon. Testing with lithium button cells shows that when this carbon powder is used as an electrode, the reversible specific capacity at 0.2C is 356 mAh / g.
[0081] Example 12: The battery black powder is subjected to supercritical reduction treatment with additive assistance, specifically as follows: ①Wet process reaction: 500g of waste battery black powder (a mixture of positive electrode NCM111 and negative electrode carbon powder, as well as a small amount of binder, conductive agent, and metal current collector) is placed into a 1L reactor. The reactor is made of Inconel 625 alloy. 400mL of water, 40g of diethyl carbonate and 15g of methanol are introduced into the reactor. The reactor is sealed, and the heating furnace and constant flow pump are turned on to heat and pressurize the reactor. The reactor temperature is maintained at 450℃ and the pressure is maintained at 35MPa. The reaction is carried out under these conditions for 3h. ② Solid-liquid separation: After the reaction is completed, wait for the temperature inside the vessel to drop to room temperature, open the exhaust valve, and after the pressure drops to atmospheric pressure, open the reaction vessel, collect the solution inside the vessel and filter it to obtain a lithium-containing solution and a pot of reduction residue; ③ Lithium carbide precipitation: Add excess Na2CO3 (excess coefficient 1.50) to the above lithium-containing solution, stir at 90℃ for 30 min, and filter while hot to obtain Li2CO3; ④ After drying the slag phase (one-pot reduction slag) from the previous step, perform routine dispersing treatment, and then carry out acid leaching. Specifically, add it to 500 mL of 1 mol L⁻¹ solution at a liquid-to-solid ratio (mL:g) of 20:1. -1 In an H2SO4 solution, the mixture was heated to 60°C and reacted for 1 hour. After filtration and washing, acid leaching solution and acid leaching residue were obtained, and solid-liquid separation was performed on them. Solid-liquid separation yields a leachate. The leachate is first subjected to Na soap-treated P2O4 to extract manganese, followed by back-extraction to obtain a manganese sulfate solution. Then, it is subjected to saponified P5O7 to extract cobalt, followed by back-extraction to obtain a cobalt sulfate solution. The cobalt-extracted solution is then subjected to saponified P5O7 to extract nickel, followed by back-extraction to obtain a nickel sulfate solution. See Example 1 for details.
[0082] ICP results showed that the leaching rates of manganese, cobalt, and nickel were 99.8%, 99.7%, and 99.5%, respectively. In addition, the lithium extraction rate was 99.2%, and the recovery rates of copper foil and aluminum foil were 99.3% and 99.5%, respectively.
[0083] The slag phase obtained from solid-liquid separation was subjected to conventional drying and dispersion. The results showed that the fixed carbon content in the obtained carbon powder was 99.8%. Tests on lithium button half-cells showed that when this carbon powder was used as an electrode, the reversible specific capacity of the electrode under 0.2C conditions was 356 mAh / g.
[0084] Comparative Example 1: Compared with Example 12, the only difference is that diethyl carbonate and methanol additives were not added during the supercritical treatment process. The difference lies in step ①, which is a wet process reaction: 500g of waste battery black powder is placed in a 1L reactor. The reactor is made of Inconel 625 alloy. 400mL of water is introduced into the reactor. The reactor is sealed, and the heating furnace and constant flow pump are turned on to heat and pressurize the reactor, maintaining the reactor temperature at 450℃ and the pressure at 35MPa. The reaction is carried out under these conditions for 3 hours. Other processes are the same as in Example 12.
[0085] ICP results showed that the leaching rates of manganese, cobalt, and nickel were 56.1%, 57.5%, and 56.3%, respectively. The extraction rate of lithium was 67.4%, and the recovery rates of copper foil and aluminum foil were 89.1% and 79.3%, respectively.
[0086] The slag phase obtained from solid-liquid separation was subjected to conventional drying and dispersion. The results showed that the fixed carbon content in the obtained carbon powder was 72.1%. Tests on lithium button half-cells showed that when this carbon powder was used as an electrode, the reversible specific capacity of the electrode under 0.2C conditions was 223 mAh / g.
[0087] Therefore, it is evident that directly using the disassembled electrode powder as the reaction raw material, which contains virtually no electrolyte and no additives are added to the reaction system, failed to achieve the expected recovery effect using the aforementioned technology.
[0088] Comparative Example 2: Compared with Example 1, the only difference is that the temperature and pressure in step ② did not meet the requirements of this invention. The difference in step ② is as follows: the above-mentioned waste battery cells are placed in a 1L reactor. The reactor is made of Inconel 625 alloy. 400mL of water is introduced into the reactor to submerge the waste battery cells. The reactor is then sealed. The heating furnace and constant flow pump are turned on to heat and pressurize the reactor. The reactor temperature is maintained at 200℃ and the pressure is 5MPa. The reaction is carried out under these conditions for 3 hours. All other steps and processes are the same as in Example 1.
[0089] Tests showed that the leaching rates of manganese, cobalt, and nickel were 66.2%, 71.5%, and 42.7%, respectively. In addition, the lithium extraction rate was 69.93%, and the recovery rates of copper foil and aluminum foil were 79.1% and 79.3%, respectively.
[0090] The slag phase obtained from solid-liquid separation was subjected to conventional drying and dispersion. The results showed that the fixed carbon content in the obtained carbon powder was 79.7%. Tests on lithium button half-cells showed that when this carbon powder was used as an electrode, the reversible specific capacity of the electrode under 0.2C conditions was 262 mAh / g.
[0091] It is evident that without reaching supercritical processing conditions, the leaching rate of valuable metals is low, the resulting carbon powder has a high impurity content, and its electrochemical performance is poor.
[0092] Comparative Example 3: Supercritical treatment in oxidation systems ①Physical discharge: The waste nickel-cobalt-manganese ternary lithium batteries are directly physically discharged to 0.2V, and the plastic shell is manually removed to obtain 40g of waste battery cells; ②Wet process reaction: Place the above-mentioned waste battery cells into a 1L reactor. The reactor is made of Inconel 625 alloy. 400mL of water and 50mL of hydrogen peroxide are introduced into the reactor to submerge the waste battery cells. After sealing the reactor, turn on the heating furnace and constant flow pump to heat and pressurize the reactor. Oxygen is introduced into the system to maintain the reactor temperature at 400℃ and the pressure at 35MPa. Under these conditions, the reaction is carried out for 3 hours. ③ Solid-liquid separation: After the reaction is completed, wait for the temperature inside the vessel to drop to room temperature, open the exhaust valve, and after the pressure drops to atmospheric pressure, open the reaction vessel, collect the solution inside the vessel and filter it to obtain a lithium-containing solution and a pot of reduction residue; ④ Lithium carbide precipitation: Add excess Na2CO3 (excess coefficient 1.50) to the above lithium-containing solution, stir at 90℃ for 30 min, and filter while hot to obtain Li2CO3; ⑤ After drying the slag phase (one pot of reduction slag) from the previous step, perform conventional dispersing treatment, and then place it in a vibrating separator screen for vibrating treatment. The screen mesh size of the vibrating separator screen used in this step is 240-400 mesh. The material on the screen is large copper foil and aluminum foil, and the material under the screen is electrode powder. ⑥ Perform acid leaching on the electrode powder obtained in the previous step, take an appropriate amount of the above-mentioned first-pot reduction residue, and add it to 500 mL of 1 mol L⁻¹ solution at a liquid-to-solid ratio (mL:g) of 20:1. -1 In an H2SO4 solution, the mixture was heated to 60°C and reacted for 1 hour. After filtration and washing, acid leaching solution and acid leaching residue were obtained, and solid-liquid separation was performed on them. Solid-liquid separation yields a leachate. The leachate is first subjected to Na soap-treated P2O4 to extract manganese, followed by back-extraction to obtain a manganese sulfate solution. Then, it is subjected to saponified P5O7 to extract cobalt, followed by back-extraction to obtain a cobalt sulfate solution. The cobalt-extracted solution is then subjected to saponified P5O7 to extract nickel, followed by back-extraction to obtain a nickel sulfate solution. See Example 1 for details.
[0093] Tests showed that the leaching rates of manganese, cobalt, and nickel were 56.6%, 61.2%, and 62.4%, respectively. In addition, the extraction rate of lithium was 72.93%, and the recovery rates of copper foil and aluminum foil were 65.1% and 72.2%, respectively.
[0094] The slag phase obtained from solid-liquid separation was subjected to conventional drying and dispersion. The results showed that the fixed carbon content in the obtained carbon powder was 73.7%. Tests on lithium button half-cells showed that when this carbon powder was used as an electrode, the reversible specific capacity of the electrode under 0.2C conditions was 241 mAh / g.
[0095] It is evident that without reaching supercritical processing conditions, the leaching rate of valuable metals is low, the resulting carbon powder has a high impurity content, and its electrochemical performance is poor.
Claims
1. A method for supercritical water reduction and recycling of waste lithium-ion batteries, characterized in that, The mixture of waste lithium-ion battery cells and water is heated to the supercritical state of water in a sealed container to carry out a supercritical reduction reaction. After the reaction is completed, a lithium-rich solution, a current collector, and a delithiated electrode material are separated from it. The battery cell comprises a positive electrode, a separator, and a negative electrode sequentially laminated together, and an electrolyte solution soaking the positive electrode, separator, and negative electrode; the battery cell is a complete, unbroken battery cell. The temperature of the supercritical state is 405℃~750℃, and the pressure is 25~50MPa; The supercritical reduction reaction time is 2~10 h; The mixture also contains an additive; the additive is at least one of alcohols, ethers, esters, nitriles, and ketones with 20 or fewer carbon atoms. The alcohol is at least one of C1-C6 units or polyols; The ether is at least one of a C2-C6 monoether, polyether, or cyclic ether; The ester is C2~C 10 Carboxylic acid esters, C3~C 10 At least one of the carbonates; The nitrile is a C2-C4 nitrile; The ketone is C3~C 10 At least one of monoketones, polyketones, and cyclic ketones; The weight ratio of the additive to the battery cell is 0.01 to 1:
1.
2. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 1, characterized in that, The residual voltage of the battery cell is less than or equal to 1V.
3. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 2, characterized in that, The residual voltage of the battery cell is 0~0.5V.
4. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 3, characterized in that, The residual voltage of the battery cell is 0~0.1V.
5. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 1, characterized in that, The waste lithium-ion batteries mentioned are at least one of the following: waste nickel-cobalt-manganese ternary batteries, lithium iron phosphate batteries, lithium cobalt oxide batteries, and lithium manganese oxide batteries.
6. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 1, characterized in that, The solid-liquid ratio of the battery cell and water is (0.1~25)g:100ml.
7. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 6, characterized in that, The solid-liquid ratio of the battery cell to water is (5~10)g:100ml.
8. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 1, characterized in that, The additive is at least one of methanol, ethanol, carbonate, diethyl ether, acetonitrile, and acetone.
9. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 1, characterized in that, The weight ratio of the additive to the battery cell is 0.2~0.5:
1.
10. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 1, characterized in that, The temperature of the supercritical state is 550~750℃; the pressure is 25~50 MPa.
11. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 1, characterized in that, The supercritical reduction reaction time is 5-8 hours.
12. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 1, characterized in that, The system after the supercritical reduction reaction is sieved to obtain the current collector sieve residue and the slurry containing electrode materials. Solid-liquid separation of the slurry yields a lithium-rich solution and delithiated electrode material; Alternatively, the system after the supercritical reduction reaction can be subjected to solid-liquid separation to obtain a lithium-rich solution and reduction residue. The reduction residue can then be dried and sieved to obtain a current collector and a delithiation electrode material.
13. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 1, characterized in that, The lithium-rich solution is subjected to lithium precipitation treatment to recover the lithium.
14. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 13, characterized in that, Add a lithium precipitation agent to a lithium-rich solution to perform lithium precipitation treatment and recover the lithium therein; The lithium precipitation agent is at least one of sodium carbonate and potassium carbonate.
15. The supercritical water reduction and recycling method for waste lithium-ion batteries as described in claim 1, characterized in that, The delithiation electrode material was subjected to acid leaching, followed by solid-liquid separation to obtain the electrode material leachate and carbon slag.
Citation Information
Patent Citations
Device and method for extracting metals from electronic waste by supercritical water process
CN104962746A
Method for transcritical fluid enhanced separation of positive active material and aluminum current collector in waste lithium ion battery
CN113381088A
Method for processing accumulators, batteries and the like, and system for carrying out the method
WO2021009199A1